Navigating ambiguous waters: a relational approach to nested conflicts in the Katari River Basin, Bolivia - Afnan Agramont; Leonardo D. Villafuerte Philippsborn; Guadalupe Peres-Cajias; Analy Baltodano Martinez; Ann van Griensven; Marc Craps; Marcela F. Brugnach (Ecology and Society)
The Katari River Basin, the most densely populated basin in Bolivia, discharges into Lake Titicaca, the world’s highest navigable lake and a crucial water resource in the Andes. Despite its significance, the basin suffers from severe water contamination because of anthropogenic activities. This pollution adversely affects water quality, distribution, and availability, exacerbating the region’s vulnerability to the impacts of climate change at high elevations. In response to these challenges, the Bolivian government established a multi-stakeholder platform. However, this platform reveals complex water conflict dynamics linked to ambiguity associated with different ways of knowing, framing, and coping with water pollution issues. This study examines how relational practices are linked to managing ambiguity and addressing nested water conflicts. Relational practices are communication-based practices by which the involved actors shape and develop mutual and shared sense-making relationships. Our findings reveal that current relational practices hinder their ability to collaboratively address ambiguities, leaving underlying water conflicts unresolved. Moreover, they indicate that ambiguity is managed by imposing a singular frame, reinforced by the significant power asymmetries within the multi-stakeholder platform, strengthening the dynamics of water conflicts. We conclude that dealing with ambiguity through high-quality relational practices could facilitate the recognition and resolution of water conflicts, potentially improving clarity, communication, and advancing collaborative problem-solving among stakeholders.